A single-center rheumatology experience of sarcoidosis: observations from 70 patients - Konak, Hatice Ecem; Güven, Serdar Can; Atalar, Ebru; Akyüz Dağlı, Pınar; Koçak Ulucaköy, Rezan; Kayacn Erdoğan, Esra; Babaoğlu, Hakan; Orhan, Kevser; Doğan, İsmail and Maraş, Yüksel and Omma, Ahmet and Küçükşahin, Orhan and Erten, Şükran (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
Background: The aim of this study is to determine the demographic, clinical and laboratory characteristics of the patients who followed up with the diagnosis of sarcoidosis, to investigate the distribution frequency of rheumatological findings and to examine the disease management from the perspective of rheumatology. Methods: Patients who were followed up with the diagnosis of sarcoidosis in the rheumatology clinic of Ankara City Hospital between November 2019 and November 2022 were evaluated. Demographic, clinical, radiological, serological, laboratory, and histopathological findings, and rheumatological, systemic, and locomotor system examination findings of the patients were obtained from the medical data registered in the hospital. Results: A total of seventy sarcoidosis patients (48.98 ± 11.78 years, %75 female) were included in the study. Joint involvement was observed in 64.3% of cases, skin involvement in 48.6% of cases, and ocular involvement in 25.7% of cases. The ankle was the most frequently involved joint, followed by the knee and small joints in the foot. Corticosteroids were the most used therapeutic agent, and pulmonary and joint findings were the most common reasons for starting treatment. Conclusions: Sarcoidosis is a disease that mimics many diseases, misdiagnosis and treatment should be avoided with a good and fast differential diagnosis. Clinicians, especially rheumatologists, should remember sarcoidosis more frequently and keep it in mind in the differential diagnosis.